MENINGKATKAN EFISIENSI LINTASAN KERJA MENGGUNAKAN METODE RPW DAN KILLBRIDGE-WESTERN - Firman Ardiansyah Ekoanindiyo; Latif Helmy (Jurnal Ilmiah Dinamika Teknik, 2017)
Line Balancing the flow of the production process is still often ignored by the company both fabrication and assembly. That is because the balance of the trajectory associated with the production output is achieved. Current CV. MJ less able to meet the target of maximum production, which is to meet the demand of consumers. This is due to the difference in production output at each work station resulting in the accumulation of material work. To be able to calculate the measurement line balancing the working time of each operation in wilson product folding chair in the assembly department by using stopwatch. The method used in solving the problem of balancing this is the method Ranked Positional Weight and methods Killbridge-Western. Ranked Positional Weight Method is a method that calculates the cycle time, the matrix precursor based network, compute weight position, time efficiency average. From the calculation results after using the Ranked Positional Weight and methods Killbridge-Western obtained value balance delay 15:41%, 84.59% system efficiency, output produced 142.14 seat unit / day by the number of work stations 6. And to have better results than before using both methods. So should the company implement Ranked Positional Weight methods and methods Killbridge-Western because it can reduce the delay balance, improve system efficiency and increase production output. Keywords : Line Balancing, Ranked Positional Weight Method, Killbridge-Western Method.